Cephalometrıc Evaluatıon Of The Nasal Aırway Capacıty Before And After Adenoıdectomy In Mouth Breathıng Syndrome - Deniz Sağdıç; Osman Bengi; Hüseyin Ölmez; Faik Korunmuş (Turkish Journal of Orthodontics, 1996)

(untitled)
The purpose of this study is to evaluate the importance of cephalometric analysis for indication of adenoidectomy in mouth breathing which is caused by nasopharingeal blokage. Our investigation was carried on 20 lateral cephalograms of 10 indivudials which were obtained before and after adenoidectomy operations. In cephalometric evaluation, the nasal airway percentage, AD1-PNS, AD2-PNS and PtV-AD distances were measured and compared with the norms. The nasal airway percentage was calculated by aplanimeter and by the help of a computer system. Postoperatif measurements emphasized the elemination of adenoidal blokage and the similarity of our findings with the norms of Michigan University.